(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article tells about the works on Shevchenkoʼs studies, published in the journals «Shevchenko and his time» (1925, 1926) of such researchers as P. Filipovich, I. Hermajze, V. Petrov, A. Loboda, A. Doroshkevich, S. Rodzevich. The scientific preferences of the authors of the journals in the field of Shevchenko studies are considered and their contribution to the study of the creativity of T. Shevchenko and his personality is analyzed.